Angle distortion model for predicting enediyne activation towards Bergman cyclization: an alternate to the distance theory. Issue 36 (18th August 2022) - Bhattacharya, Prabuddha; Chakraborty, Soham; Balaji, Ashwin; Basak, Amit
Abstract : Structurally similar enediynes showed decrease in interior proximal bond angles ( P a and P b ) with increase in reactivity. Enediynes with average interior proximal angles [( P a + P b )/2] less than 166° undergo cyclization under ambient conditions. Abstract : The kinetics of Bergman cyclization (BC) of enediynes into 1, 4-benzene diradicals (also known as p -benzynes) have attracted interest ever since the discovery of natural enediynes which pointed out a surprising reactivity profile difference across enediynes with varying structural architectures. From the analysis of experimental kinetic data, several models were proposed to have a structure-kinetics correlation, out of which, the cd-distance model and the transition state model are the most accepted ones. Recently, Houk et al. introduced a distortion model to explain the regioselectivity of nucleophilic addition to unsymmetrical o -benzynes based on the geometry of the transition state. In the case of BC, since the reaction is endothermic, the transition state geometrically resembles the product structure which implies that in the reaction pathway, the sp-carbons of enediynes are transformed into the trigonal sp 2 carbons of the benzenoid product. Thus, greater bending of the interior angles at the proximal alkyne carbons in the enediynes will lead to a lower activation barrier for the BC and hence faster cyclization. This hypothesis has been tested on a series of enediynes including natural product surrogates and the extent of deviation correlates well with the kinetic results. A cut-off value for the average internal proximal angles has been proposed to categorize enediynes as per their reactivity under ambient conditions. We believe that this distortion theory offers an alternative model in designing new unnatural enediynes with desired kinetic stabilities.